Prevalence and predictors of men's involvement in pregnancy care in Modakeke, Southwest Nigeria - Akinyemi, Aminat Omolara; Ibrahim, Elhakim Adekunle (Frontiers in Global Women's Health, 2024)
Introduction Maternal mortality in developing countries remains a major public health concern and lack of men's support for their spouse during pregnancy contributes to this adverse outcome. This study examined the level and determinants of men's involvement in pregnancy care in Modakeke, Southwest Nigeria. Methods A community-based cross-sectional, mixed-methods study involving quantitative and qualitative data. A multistage sampling strategy was used to select the study participants. The study involved 414 male respondents interviewed using a structured interviewer-administered questionnaire. The interview was complemented with one focus group discussion facilitated using an unstructured interview guide. Quantitative data were analyzed using descriptive and inferential analytical techniques while qualitative data were explored using thematic content analysis. Results Findings revealed a 55% level of involvement in pregnancy care among the participants. However, involvement rates were higher among those who were younger, married, from monogamous family, with secondary or tertiary education, low-income earners, and holding positive perception about nontraditional gender roles. Multivariate logistic regression estimates indicated significantly lower odds of involvement among unmarried men than the married but increased odds among those who had secondary or higher education relative to the uneducated, and among those whose partners received antenatal care from multiple providers compared to from health facilities only. Furthermore, significantly reduced odds of involvement were associated with holding nonpositive perceptions towards accompanying spouse to antenatal care clinic and being involved in general pregnancy care as opposed to holding positive perception. Perceived challenges undermining male involvement as highlighted during focus group discussion include time constraints due to job demands, prohibitive sociocultural norms, rebuke and unconducive health facility environment. Conclusion The level of involvement in pregnancy care is suboptimal among the study participants with considerable sociodemographic, socioeconomic and sociocultural dimensions. Enhancing men's involvement in pregnancy care requires community-based awareness-raising interventions that emphasize crosscutting benefits of male partner's participation in pregnancy-related care and address known sociocultural barriers impeding active involvement.